Adaptive surface distortions for torque ripple control in vertical-axis wind turbines. Issue 2 (April 2021) - Erfort, Gareth; von Backström, Theodor W; Venter, Gerhard
Vertical-axis wind turbines have been confined to small-scale generation in urban environments where their omnidirectional capability offers them an advantage over the more ubiquitous horizontal-axis wind turbine. With a drive towards renewable energy, more opportunities exist for the implementation of wind turbines in a multitude of environments. Based on its inherent operational drawbacks, the vertical-axis wind turbine has not undergone extensive investigation. Recently, there has been a resurgence of interest in the technology. This article addresses the torque ripple, a variation in torque produced by the turbine, present during operation. The variation in torque generated by a vertical-axis wind turbine increases the likelihood of failure due to fatigue. Current treatment is symptomatic and addresses the result of the torque fluctuation and not the cause. A novel blade design, capable of altering the lift and drag response through shape alteration, is presented as a solution. The blade design and operation is achieved through genetic algorithm optimization and computational fluid dynamic simulations. Comparisons with previous work show the novel blade presented here surpasses the reduction seen with pitching solutions. A 25% reduction in torque ripple was demonstrated for a 17% reduction in performance coefficient using the surface distortion approach. This surpasses the foil pitching approach which achieved a 15% torque ripple reduction for the same loss in performance coefficient.